1999
DOI: 10.1097/00006123-199903000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Shunt-dependent Hydrocephalus after Early Surgical and Early Endovascular Treatment of Ruptured Intracranial Aneurysms

Abstract: The results of the present study indicate that the treatment method used does not affect the risk of the later development of chronic shunt-dependent hydrocephalus (early surgery, 23.2% [29 of 125]; early endovascular treatment, 17.7% [11 of 62]; P = 0.45).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
83
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 28 publications
11
83
2
Order By: Relevance
“…Dorai et al 5) stated that 1.3% of shunt-treated patients were in FG 1, whereas 86% of patients were reported as FG 3. Also, the influence of the quantity of blood in the subarachnoid space was supported by results from many other studies 7,8,12,18) . Our results showed a total rate of SDHC of 19.7%, which was consistent with results from other series found in the literature 4,5,8,16) .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Dorai et al 5) stated that 1.3% of shunt-treated patients were in FG 1, whereas 86% of patients were reported as FG 3. Also, the influence of the quantity of blood in the subarachnoid space was supported by results from many other studies 7,8,12,18) . Our results showed a total rate of SDHC of 19.7%, which was consistent with results from other series found in the literature 4,5,8,16) .…”
Section: Discussionsupporting
confidence: 59%
“…Most reports revealed that endovascular coiling could be attributed to an increased rate of SDHC 4,5,19) . However, Gruber et al 8) reported that the endovascular treatment group did not suffer SDHC more frequently than the surgical treatment group.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations